Gulf Economic Monitor, Issue 4 : Building the Foundations for Economic Sustainability - World Bank Group (World Bank, Washington, DC, 2019)
The economies of the GCC recovered in 2018 despite signs of weakness in the global economic outlook, reinforcing the perception that GCC economies' fortunes are still inextricably tied to oil. Global growth slowed in 2018, as trade tensions be-tween the U.S. and China escalated, and goods trade slowed markedly. However, the steady increase in oil prices until October 2018 lifted growth in the GCC economies, from an average of -0.2 percent in 2017 to 2.0 percent in 2018. Two of the region's largest economies Saudi Arabia and Kuwait, as well as Oman, emerged from recession in 2018. Growth outturns were driven by higher oil production in the second half of 2018, higher capital investment made possible due to the rise in oil revenues, and higher domestic demand. Fiscal and external balances improved, also tracking oil sector performance. GCC countries' fiscal balances improved in 2018, aided by the average increase in oil prices and progress with non-oil revenue mobilization in some countries. This allowed most countries to reduce fiscal deficits while actually increasing spending in some cases. Saudi Arabia, for example was able to halve its overall fiscal deficit in 2018 while simultaneously increasing total spending by 10.8 percent. Other countries also demonstrated procyclicality in fiscal policy, as spending increased across the GCC. Saudi Arabia and the UAE implemented a 5 percent VAT in early 2018, and Bahrain followed in early 2019. Oman introduced excise taxes on tobacco products, energy drinks and soft drinks in mid-2018 and increased corporate income tax.